Growth and bioactivity of Phellinus linteus in the mushroom farm, at different cultivation times - Jitchum Supapitch; Tabtimmai Lueacha; Phoohinkong Weerachon; Thumthanaruk Benjawan; Zhang Xiaoshuan; Suttisintong Khomson; Rungsardthong Vilai (E3S Web of Conferences)
Phellinus linteus (PL) growth depends on environmental conditions such as light intensity, humidity, temperature, and CO2. This research investigated the growth of PL and their bioactive activities in the PL fruiting body from different locations of Top, Middle, and Bottom zones in the mushroom farm, harvested at different cultivation times, up to 18 months. Results showed that PL weights increased from 9.35 g/fruiting body to 46.89 g/fruiting body at 18 months. PL growths at each location were not significantly different during 12 months, while a bit higher growth of PL at the Bottom zone was observed at 18 months. The temperature during the cultivation was 30-35°C with high humidity (83-100%). The Bottom zone indicated the higher CO2 than the other two zones. The bioactivity in PL extracts from the cultivation during at 3-18 months showed a non-significant difference in both TPC, and antioxidant activities analyzed by DPPH. PL extract presented an anti-inflammatory effect comparable to the medicine diclofenac. The potential applications of PL extract inhibit cancer; particularly, the low survival rate of cell cancer by the PL extract present its possible use as a functional ingredient. Further studies of their toxicity on normal cells would benefit the application of PL extract.